Science dialogues: Talking about science - Roper, Juliet; Weaver, Kay; Zorn, Ted (New Zealand Science Review, 2005)
​To promote greater social discussion of science, bringing together scientists and members of the public in face-to-face dialogue might seem like an obvious idea. However, for many people science is a complicated subject that they do not necessarily feel able to talk about, and scientists are not always good at talking about what they do. Researchers from the Department of Management Communication at Waikato Management School are looking for ways to enhance public involvement in science issues and to get scientists to share their specialist knowledge more widely in a ‘user-friendly’ way.